Re-establishing research in Rwanda - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1995)
One of the biggest tasks facing the new government of Rwanda is ensuring food security. Before the war Rwanda's national agricultural research system, L'Institut Scientifique d'Agriculture Rwandaise (ISAR), was involved in numerous research...